ASSESMENT OF RENEWABLE ENERGY TECHNOLOGIES (SOLAR THERMAL AND WINDMILS) - Togar Wiliater Soaloon Panjaitan (Institute of Research and Community Outreach - Petra Christian University, 2005)
The development of renewable energy technologies (RETs) has moved forward significantly; while the current environmental problems that some attribute to, among others, the combustion of fossil fuels to produce energy has contributed to the attractiveness these technologies. In some instances, governments support RETS and have put in place subsidies to encourage people and companies to implement or use them. Companies have responded to this as it not only brings monetary savings from using energy efficiently but can also be valuable for their image as more and more consumers are becoming environmentally conscious. Many companies have decided to take a similar route and is interested in using RETS and other environmentally friendly technologies to meet its energy requirements. The report has addressed the issue of looking at the technical and financial feasibility of installing some or all of the identified renewable energy technologies (wind energy and solar thermal), and has been structured in line with the following approach. In this report, the following approach/preliminary assessment method based on Investment Costs, O & M Costs, Operational hours/year, Ease of Installation, O&M Procedures, Social Acceptability, Greenness of technology.